Creative thinging: the feeling of and for clay - Malafouris, L (John Benjamins Publishing, 2014)
Humans are organisms of a creative sort. We make new things that scaffold the ecology of our minds, shape the boundaries of our thinking and form new ways to engage and make sense of the world. That is, we are creative ‘thingers’. This paper adopts the perspective of Material Engagement Theory (Malafouris 2013) and introduces the notion ‘thinging’ to articulate and draw attention to the kind of cognitive life instantiated in acts of thinking and feeling with, through and about things. I will focus more specifically on Creative thinging, or creative material engagement, exploring the importance of thinging for understanding our species unique capacity for inventiveness.